Identification of preferred multimodal ligand‐binding regions on IgG1 FC using nuclear magnetic resonance and molecular dynamics simulations. Issue 2 (6th November 2020) - Gudhka, Ronak B.; Bilodeau, Camille L.; McCallum, Scott A.; McCoy, Mark A.; Roush, David J.; Snyder, Mark A.; Cramer, Steven M.
Abstract: In this study, the binding of multimodal chromatographic ligands to the IgG1 FC domain were studied using nuclear magnetic resonance and molecular dynamics simulations. Nuclear magnetic resonance experiments carried out with chromatographic ligands and a perdeuterated 15 N‐labeled FC domain indicated that while single‐mode ion exchange ligands interacted very weakly throughout the FC surface, multimodal ligands containing negatively charged and aromatic moieties interacted with specific clusters of residues with relatively high affinity, forming distinct binding regions on the FC . The multimodal ligand‐binding sites on the FC were concentrated in the hinge region and near the interface of the CH 2 and CH 3 domains. Furthermore, the multimodal binding sites were primarily composed of positively charged, polar, and aliphatic residues in these regions, with histidine residues exhibiting some of the strongest binding affinities with the multimodal ligand. Interestingly, comparison of protein surface property data with ligand interaction sites indicated that the patch analysis on FC corroborated molecular‐level binding information obtained from the nuclear magnetic resonance experiments. Finally, molecular dynamics simulation results were shown to be qualitatively consistent with the nuclear magnetic resonance results and to provide further insights into the binding mechanisms. An important contribution to multimodal ligand‐FC binding in these preferred regions was shown to be electrostatic interactions and π–π stacking of surface‐exposed histidines with the ligands. This combined biophysical and simulation approach has provided a deeper molecular‐level understanding of multimodal ligand–FC interactions and sets the stage for future analyses of even more complex biotherapeutics. Abstract : A combined biophysical and simulations approach is described for identifying preferred binding regions on IgG1 FC domain in multimodal (MM) chromatography. Gudhka and coworkers perform NMR experiments with 15N‐labeled FC and MM chromatographic ligands in free solution to identify the hinge region and the interface of the CH2 and CH3 domains to be the preferred binding regions on the protein surface. Comparison of this result with the protein surface property map suggests that these binding regions correspond well with the overlapping regions of positive charge and hydrophobicity. Finally, by performing MD simulations, authors provide insights into the binding mechanisms and also show a few docked poses of the MM ligands on the FC surface.